Relasi Agama dan Sains dalam Studi Ayat-Ayat Kauniyah: Tinjauan Epistemologis antara Ulumul Qur’an dan Empirisme David Hume - Tazkiyah, Dewy Wardah; Hidayah, Khairu Ramadani Nurul; Bariroh, Umi (SENTRI: Jurnal Riset Ilmiah, 2025)
This study analyzes the relationship between David Hume's empiricism and the Qur'an by making Hume's critique of causation and miracles the main unit of analysis for rereading the epistemology of kauniyah verses in the perspective of Qur'anic sciences. The purpose of this research is to explain how Hume's concept of empiricism can open a space for epistemological dialogue with the Islamic scientific tradition and clarify the boundary between empirical and theological explanations in understanding natural phenomena and miracles. The method used is a qualitative approach through literature study, philosophical analysis, and epistemological comparison between Hume's thought and the discipline of Ulumul Qur'an, especially related to the source of knowledge, validity of experience, and the concept of natural order. The findings of the study suggest that Hume's critique of cause and effect helps reinforce the urgency of empirical verification in understanding natural phenomena, while at the same time confirming that miracles are in a transcendent realm that cannot be tested with empirical instruments. In addition, the study found that many of Hume's principles can be a critical mirror to avoid excessive scientific analysis of the Qur'an, but still encourage the scientific and responsible reading of kauniyah verses. The contribution of this research lies in strengthening the interdisciplinary methods between Western philosophy and the Qur'an, offering a more balanced framework of dialogue between modern empiricism and Qur'anic epistemology.